Roles of clinical faculty in promoting the practice of patient safety by nursing students - Feni Betriana; Kittikorn Nilmanat (Jurnal Keperawatan Padjadjaran, 2023)
Patient safety is a major concern in nursing and healthcare delivery. It is related to the quality of care and is the responsibility for all healthcare professionals. As the users of healthcare services for educational purposes, nursing faculty and nursing students practicing in the hospital carry the responsibility of their practice for the sake of patient safety. While patient safety has been taught in nursing school, it is important to ensure that this topic is well practiced by nursing students in their clinical practicum. The nursing faculty plays an important role in this regard. This editorial proposes the roles of clinical faculty in promoting the practice of patient safety by nursing students through various teaching modalities. By understanding and implementing the roles, clinical faculty is expected to ensure that nursing students are able to promote patient safety during their clinical practice.